Integrated Functional Neuroimaging, Monoamine Neurotransmitters, and Behavioral Score on Depressive Tendency in Intensive Care Unit Medical Staffs Induced by Sleep Deprivation After Night Shift Work - Ye, Haotian; Ji, Muhuo; Wang, Chaoyan; Wang, Cong; Li, Ying; Chen, Yuan; Cheng, Lisha; Li, Yanfei; Yang, Jian-Jun (Frontiers in Psychiatry, 2022)
ABSTRACT Background: ICU medical staffs undergoing sleep deprivation with perennial night shift work were usually at high risk of depression. However, shift work on depression-related resting-state functional magnetic resonance imaging (rs-fMRI) was still not be fully understood. The objective of this study was to explore the effects of sleep deprivation in ICU medical staffs after one night of shift work on brain functional connectivity density (FCD) and Hamilton Depression Rating Scales (HAMD) scores. Also, serum neurotransmitters concentrations of serotonin (5-HT) and norepinephrine (NE) were obtained simultaneously. Methods: A total of 21 ICU medical staffs without psychiatric history were recruited. All participants received HAMD score assessment and rs-fMRI scans at two time points: one at rested wakefulness (RW) and the other after sleep deprivation (SD) accompanied with one night of shift work. Global functional connectivity density (gFCD), local FCD (lFCD), and long range FCD (lrFCD) were used to evaluate spontaneous brain activity in the whole brain. In the meantime, peripheral blood samples were collected for measurement of serum 5-HT and NE levels. All these data were acquired between 7:00 am and 8:00 am to limit the influence of biological rhythms. The correlations between the FCD values and HAMD scores, serum levels of neurotransmitters were analyzed concurrently. Results: Functional connectivity density mapping (FCDM) manifested that gFCD was decreased in the right medial frontal gyrus and the anterior cingulate gyrus, while lrFCD was decreased mainly in the right medial frontal gyrus. Most of these brain areas with FCD differences were components of the default mode network (DMN) and overlapped with medial prefrontal cortex (mPFC). The lrFCD in the medial frontal gyrus showed a negative correlation with HAMD scores after SD. Compared with RW, serum levels of 5-HT and NE decreased significantly while HAMD scores were higher after SD within subjects. Conclusions: Our study suggested that sleep deprivation after night shift work can induce depressive tendency in ICU medical staffs, which might be related to alterative mPFC, raised HAMD scores and varying monoamine neurotransmitters.